Penyuluhan Tentang Pentingnya Vaksinasi Covid 19 di Desa Mantantimali Kecamatan Marawola Barat Kabupaten Sigi Sulawesi Tengah - Imelda Kantohe (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Covid-19 has attacked Indonesia since early 2020 and the positive confirmation number continuesto increase until now. In February 2022, the total number of positive confirmations in Indonesia was 6,001,751with deaths reaching 154,774 deaths. In Central Sulawesi alone positive confirmed cases reached 60,256 caseswith deaths reaching 1,701 deaths as of March 2022 (Dinkes Prov.Sulteng, 2022). SARSCoV-2, the virus thatcauses Covid-19, can pass from human to human very quickly through the mucous membranes of the mouth,nose and eyes in the form of respiratory droplets of infected individuals. So far, preventive measures have beentaken through social distancing, wearing masks when leaving the house and communicating, and alwaysmaintaining hand and body hygiene (Prastyowati, 2020). However, with the continued increase in positivecases and death rates, the production of antiviral drugs and vaccines for Covid-19 is urgently needed, wherethese vaccines are being developed by several pharmaceutical industries and the WHO. According to a WHOsurvey on the readiness of the world community to receive the Covid-19 vaccine, the readiness of the Indonesianpeople only reached 57%. According to John Hopkins, Member of the WHO Communication CenterProgramme, the level of acceptance of the Indonesian people for this vaccine is so low that the cause must beidentified so that efforts can be made to increase this acceptance. Furthermore, according to a molecularbiologist in Indonesia, one of the reasons for this low acceptance is the low level of public trust, so thegovernment must take a special approach to the community to increase this trust. In addition to trust issues,fear of a Covid-19 vaccine is also increasing. This high level of distrust and fear is largely due to the ambiguityof information received from social media. The amount of incorrect information resulted in a confusion ofinformation received by the public (Rinaldi and Yuniasanti, 2020).